Age of Diagnosis is Associated with Disease Presentation and Therapeutic Complications in Patients with Crohn's Disease. Issue 5 (26th February 2016) - Saad, Abdo M.; Czul, Frank; Sakuraba, Atsushi; Rubin, David T.; Cohen, Russell D.
Abstract: Background: Although Crohn's disease (CD) is usually diagnosed at a younger age, a growing population of patients with inflammatory bowel disease is diagnosed above age 60 (elderly). The aim of this study was to compare disease phenotype, behavior, and therapy in elderly patients with CD to young patients diagnosed between 18 to 25 years. Methods: This retrospective case–control study identified patients diagnosed with CD at age 60 or above (elderly) and matched them by gender and disease duration with 2 "young" controls diagnosed between 18 and 25 years. Demographic data, disease information, and medical and surgical history were collected from the University of Chicago Medicine inflammatory bowel disease database. Results: Thirty-two patients were identified in the "elderly" group and matched to 64 "young" patients. Crohn's colitis was more common in older patients (37.5% versus 15.6%, P = 0.02) who were also less likely to have ileocolonic, perianal, or penetrating disease with less extraintestinal manifestations. After 1998, there was no difference in the use of steroids, 5-aminosalicylates, immunomodulators, biologics, or immunomodulators + biologics. No difference was found in the rates of bowel surgery between the 2 groups. Elderly patients developed fewer therapy-related noninfectious complications and Crohn's-related abscesses. Three serious infections (staphylococcal septicemia, pneumonia, and cryptococcal meningitis) were identified in 3 elderly patients on combination immunomodulators + biologics. Conclusions: Elderly CD is more likely to present with Crohn's colitis and less likely to present with ileocolonic, perianal, or penetrating disease with less extraintestinal manifestations. Elderly are more likely to develop serious therapy-related infectious complications. Larger prospective trials are needed to evaluate the risks of CD immunosuppressive therapy in elderly patients.